An analysis of muscle tension in tandem track cyclists - Kopacz, K.; Fronczek-Wojciechowska, M.; Galczynski, S.; Prusaczyk, S.; Padula, G. (Journal of Kinesiology and Exercise Sciences, 2016)
Aim. The aim of the present study was to evaluate the level of muscle tension in tandem track cyclists on a trainer and the track. Basic procedures. Two tandem pairs were evaluated: one consisting of 2 women and the second of 2 men. Surface BTS FREEEMG300 electromyography was used to measure the muscle tension of the left and right biceps femoris, left and right gastrocnemius, left and right rectus femoris, and left and right tibialis anterior. Main findings. The greatest difference was observed in resting state in the right tibialis anterior muscle. The greatest differences between minimum and maximum values were noticed in the right biceps femoris on the trainer and right tibialis anterior on the track. Conclusions. 1. Muscle tension is higher on the track than on the trainer. 2. Any amount of muscle imbalance can impair cycling biomechanics and result in the loss of valuable seconds during competitions.